The effect of tactical exercises according to the playing areas in developing Mass attack of Youth football player - joudah, jassim majeed; abrahim , Maad salman (International Journal of Psychosocial Rehabilitation, 2020)
Research objectives: Prepare tactical exercises according to the playing areas to develop the mass attack of the youth football players,and Learn about the impact of the written exercises according to the play areas to develop the mass attack of youth football players. Conclusions: In light of the results of the tests, analysis and discussion, the researchers reached the following conclusions: The tactical exercises prepared by the researcher are effective in developing the group attack of the youth footballers, The use of tactical exercises helps the player to get rid of observing the opponent under pressure and improving the scoring skill, Similar tactical exercises that play a positive role in developing the level of offensive performance. Recommendations: Adopting the tactical exercises in the training curriculum for the first and excellent grades teams, conducting a similar study for other age groups, Generalizing tactical exercises on the females’ soccer teams.